102 THE CONDITIONAL KNOCKDOWN OF CREB USING CRE-LOX-REGULATED SHRNA. Issue 1 (1st January 2007) - Kaneko, O. F.; Cheng, J.; Sakamoto, K.
Abstract : The cyclic-AMP response element binding protein (CREB) is a transcriptional activator involved in a diverse array of functions, including glucose homeostasis, cell survival, learning, and memory. In addition, CREB also plays an important role in neoplastic hematopoiesis. Bone marrow from patients with acute leukemia overexpresses CREB compared with normal bone marrow; CREB transgenic mice in which CREB is overexpressed in myeloid cells develop myeloproliferative/myelodysplastic syndrome after 1 year. To further investigate the role of CREB in blood cell development, we used two Cre-lox-regulated lentiviral vectors to deliver short hairpin (shRNA) directed against CREB. The vectors pSICO-puro and pSICO-R allowed for the conditional activation and inactivation of shRNA expression, respectively. Both the 32D murine myeloid leukemia cell line and Ba/F3 pro-B cell line expressing the bcr-abl oncogene were transduced with either vector. Cre recombinase was subsequently introduced to the cells through viral transduction using a lenti-Cre construct. We demonstrated that CREB levels can be temporally controlled with this technique. The ability to conditionally knockdown CREB is an important tool in understanding CREB's role in normal and aberrant hematopoiesis.